EFFECT OF VITAMIN E ON INTERMOLECULAR INTERACTIONS IN ETHANOL SOLUTIONS OF SODIUM PENTADECYLSULFONATE (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
The effect of vitamin E on intermolecular interactions in ethanol–sodium pentadecylsulfonate solutions by conductivity and viscosity methods was studied. It was shown that solvophobic interactions between components of system played the main role. It was established that the complex between molecules of vitamin E and ethanol in the premicellar region of sodium pentadecylsulfonate at $(2–3)· 10^{–5} mol· L^{–1}$ concentration of vitamin E was formed. As a result, the structure of ethanol was stabilized.
Keywords: sodium pentadecylsulfonate, vitamin E, intermolecular interactions